Asymmetric Hydroacylation Involving Alkene Isomerization for the Construction of C3‐Chirogenic Center. (9th March 2021) - Liu, Chong; Yuan, Jing; Zhang, Zhenfeng; Gridnev, Ilya D.; Zhang, Wanbin
Abstract: A new transformation pattern for enantioselective intramolecular hydroacylation has been developed involving an alkene isomerization strategy. Proceeding through a five‐membered rhodacycle intermediate, 3‐enals were converted to C3 ‐ or C3, C5 ‐chirogenic cyclopentanones with satisfactory yields, diastereoselectivities, and enantioselectivities. A catalytic cycle has been theoretically calculated and the origin of the stereoselection is rationally explained. Abstract : An enantioselective intramolecular hydroacylation of 3‐enals involving alkene isomerization was developed for the efficient construction of C3 ‐chirogenic cyclopentanones with satisfactory yields, diastereoselectivities, and enantioselectivities.